Radiofrequency ablation plays double role in immunosuppression and activation of PBMCs in recurrent hepatocellular carcinoma - Zhao, Yang; Yang, Tongwang; Ouyang, Yabo; Rao, Wei; Liu, Kai; Zheng, Jiasheng; Lv, Fudong; Shi, Ying; Wang, Feng; Liu, Dongjie; Qiao, Luxin; Xia, Zhenying; et al. (Frontiers in Immunology, 2024)
Background Radiofrequency ablation (RFA) is the primary curative treatment for hepatocellular carcinoma (HCC) patients who are not eligible for surgery. However, the effects of RFA on the global tumor immune response remain unclear. Method In this study, we examined the phenotypic and functional changes in peripheral blood mononuclear cells (PBMCs) from recurrent HCC patients who had undergone two RFA treatments using mass cytometry and high-throughput mRNA assays. Results We observed significant increase in monocytes and decrease in T cell subpopulations three days after the first RFA treatment and three days after the second RFA treatment. The down-regulation of GZMB, GZMH, GZMK, and CD8A, which are involved in the cytotoxic function of T cells, was observed following RFA. Furthermore, the population of CD8 effector and memory T cells (CD8 Teff and CD8 Tem) significantly decreased after RFA. The expression of CD5 and CD161 in various T cell subpopulations also showed significant reductions. Additionally, elevated secretion of VEGF was observed in monocytes, B cells, regulatory T cells (Tregs), and CD4 naive T cells. Conclusion In recurrent HCC patients, serum components derived from radiofrequency therapy can enhance the antigen-presenting capacity of monocytes. However, they also inhibit the anti-cancer immune response by reducing the population of CD8 effector and memory T cells and suppressing the activation of T cells, as well as down-regulating the expression of CD161 and CD5 in various T cell subpopulations. These tumor-derived components also contribute to an immunosuppressive microenvironment by promoting the secretion of VEGF in monocytes, Tregs, B cells, and CD4 naive T cells.